posted by .

Evaluate each of the following. Show all your calculations.

 f" (0) if f(x) = 14x^2 + 3x − 6

• STOP! -

Please do not post any more questions until you've shown us your efforts in solving these problems.

You've received explanations for several of your problems in the last few days. Now, show us what you've learned from this help. If you've learned nothing, then I'm afraid our help is not doing you any good.

A particle is projected vertically upwards with velocity of u.after t seconds particle is projected from some point with same velocity.How long does it take for the second particle to meet the first particle?

## Similar Questions

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
2. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
3. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
4. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. f′ (3/4)if f(x) = −3x^3 − 7x^2 + 4x − 11
5. ### calculus

Evaluate each of the following. Show all your calculations. f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6
6. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6
7. ### calculus

Evaluate each of the following. Show all your calculations. f′ (3/4)if f(x) = −3x^3 − 7x^2 + 4x − 11
8. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8
9. ### calculus

Evaluate each of the following. Show all your calculations. f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6